Powerful postures do not lead to risky behaviors. (2019) - Chen, Outong; Yang, Zhaoning; Tan, Xuyun; Gu, Zibei; Chen, Jun
Recent research has found that a specific manipulation of body postures can influence psychological states associated with power, including an individual's feeling of power and risk-taking tendency, but the results vary. The purpose of this study is to replicate previous studies. A pilot experiment examined the validity of 10 postures extracted from multiple former studies. Only 4 postures were consistent with former studies. Experiment 1 replicates the study conducted by Carney, Cuddy, and Yap (2010 ). The results revealed that posture manipulations did not affect the participants' risk-taking tendency. Experiment 2 is a preregistered experiment to replicate the study of Carney et al. (2010 ). Different from Experiment 1, data were analyzed with a Bayesian approach. The results of the former study again failed to be replicated, which indicates that the posture manipulations could not yield any effect on both power feelings and individuals' risk-taking tendency. Thus, we concluded that (a) holding a specific series of body posture perceived as high or low power does not affect individuals' feeling of power, and (b) holding a specific series of body posture perceived as high or low power does not affect individuals' risk-taking tendency.